Synthesis of Some Heterocyclic Compounds Containing Two Nitrogen Atoms - PATHAK, ANIL; MOHAN MISHRA, PREM (Asian Journal of Chemistry, 2010)
Hydrazines and substituted hydrazines have tendency to take part into substitution as well as condensation reaction. The condensation with suitable carbonyl compounds give hydrazones. These hydrazones undergo cyclization under suitable conditions and form two nitrogen atom containing heterocyclic ring systems. These compounds have pronounced antibacterial properties and also acts as promoters of various organic reactions. But these are highly toxic and less curative. These compounds have a big range of biological activity due to the versatility of their application in the synthesis of drugs, polymers and dyes.